A Community Survey on Association of Sociodemographic Characteristics with Risk Perception and Awareness about Oral Cancer in Lagos, Nigeria - Afolabi Oyapero; Olufemi Erinoso; Olubukola Olatosi (Association of Support to Oral Health Research (APESB), 2024)
Objective: To assess the level of oral cancer awareness and risk factors perception and the relationship between this awareness and the sociodemographic and behavioral characteristics. Material and Methods: This descriptive study was conducted among rural and urban residents in Lagos State, Nigeria. A multi-stage random sampling method was utilized. The sociodemographic and behavioral characteristics of respondents, as well as their knowledge about oral cancer risk factors, were assessed with a validated questionnaire. The bivariate association was done using an independent t-test and one-way ANOVA. Multivariate regression was used to determine the association between predictor variables and oral cancer knowledge scores. The statistical significance level is set at p<0.05. Results: 590 participants between 18 and 82 years (mean age 34.5 ±13.7) completed the survey. The prevalence of cigarette smoking was 25.7%, of which 16 (1.5%) were heavy smokers (20+ cigarettes per day). The prevalence of alcohol consumption was 66.1%, with 57 (9.7%) being heavy drinkers, consuming drinks for 5-7 days of the week. A high proportion of the respondents (>60%) exhibited gaps in their knowledge of oral cancer. Uneducated participants had lower oral cancer knowledge than those with >12 years of formal education (aOR = 5.347; 95% CI: 4.987-6.240). Participants who were smokers had lower oral cancer knowledge compared with non-smokers (aOR = 3.341; 95% CI: 2.147-4.783); Participants who consumed alcohol had more deficient oral cancer knowledge compared with non-drinkers (aOR = 1.699; 95% CI: 1.087-2.655); While heavy smokers aOR = 4.023; 95% CI: 3.615-4.825) and heavy drinkers aOR = 4.331; 95% CI: 3.158-5.939) had lower oral cancer knowledge compared with those who did not abuse both substances. Conclusion: A high proportion of the respondents exhibited gaps in their knowledge of oral cancer in their responses. Delayed diagnosis of oral cancer can be reduced by increasing the awareness and knowledge of the populace about risk factors and also in the recognition of its signs and symptoms.